Instructional Design to Improve Students’ Entrepreneurial Affective - Dini Erlinawati; Basori Basori; Puspanda Hatta (IJIE (Indonesian Journal of Informatics Education), 2021)
The learning strategy to encourage students in building their skills through entrepreneurship practices in lined with confronting the industry 4.0 is Dual Education and Creative Products and Entrepreneurship subjects.  However, the Covid-19 pandemic generated this learning strategy cannot be implemented optimally. It has an impact on the schools, especially students, several students are less interested in entrepreneurship and they do not have job idea related to their skill after they graduate. For this reason, the Covid-19 pandemic is a significant challenge for educational institution to develop and modify entrepreneurial competencies through the digital revolution. It becomes a strategy to create students who are ready to be entrepreneurs. This study aimed to (1) determine the instructional design that can improve the students’' entrepreneurial affective, and (2) observe the instructional design on entrepreneurial affective during the study. The data collection techniques were observation, interviews and documents. The data were analyzed by the model from Miles and Huberman includes data reduction, data display and conclusions. The results revealed that (1) the instructional design for improving the students’ entrepreneurial affective at SMK N 1 Sawit is digital marketing training, and (2) the measurement of students’ entrepreneurial affective through the indicators of entrepreneurship interest, creativity and innovation as well as courage to take risks and positive thinking toward failures.